2022
DOI: 10.1021/acs.oprd.2c00108
|View full text |Cite
|
Sign up to set email alerts
|

High-Productivity Single-Pass Electrochemical Birch Reduction of Naphthalenes in a Continuous Flow Electrochemical Taylor Vortex Reactor

Abstract: We report the development of a single-pass electrochemical Birch reduction carried out in a small footprint electrochemical Taylor vortex reactor with projected productivities of >80 g day –1 (based on 32.2 mmol h –1 ), using a modified version of our previously reported reactor [ Org. Process Res. Dev. 2021 , 25 , 7, 1619–1627], consisting of a static outer electrode and a rapidly ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Since electrochemical studies revealed similar reduction potentials for both 9-methyl and 2-methyl anthracenes ðE M=M �À 1=2 ca: À 2 V vs SCE), we could not find any plausible explanation, which does not resemble pure speculation for the unsuccessful transformation of 9 into 9 a. In the case of 9-cyano-anthracene (10) and 9-chloro-anthracene (11), no de-aromatized products could be observed in the presence of PXX, and only the dimeric products were formed under both 405 and 460 nm irradiation conditions (Scheme 2). Notably, both 9-chloro-and 9-cyano-anthracenes absorb throughout the spectral blue window till 460 nm, suggesting that the kinetics of the dimerization is faster than the photoreduction also under this irradiation.…”
Section: Pxx As Homogenous Reductive Photocatalystmentioning
confidence: 78%
See 3 more Smart Citations
“…Since electrochemical studies revealed similar reduction potentials for both 9-methyl and 2-methyl anthracenes ðE M=M �À 1=2 ca: À 2 V vs SCE), we could not find any plausible explanation, which does not resemble pure speculation for the unsuccessful transformation of 9 into 9 a. In the case of 9-cyano-anthracene (10) and 9-chloro-anthracene (11), no de-aromatized products could be observed in the presence of PXX, and only the dimeric products were formed under both 405 and 460 nm irradiation conditions (Scheme 2). Notably, both 9-chloro-and 9-cyano-anthracenes absorb throughout the spectral blue window till 460 nm, suggesting that the kinetics of the dimerization is faster than the photoreduction also under this irradiation.…”
Section: Pxx As Homogenous Reductive Photocatalystmentioning
confidence: 78%
“…The loading of photocatalyst (1-10 mol %, entries 23 and 24) and HNTf 2 (0-100 mol %, Table S1 in the Supporting Information) were screened, confirming the optimal PXX concentration at 2 mol % (PXX aggregation is observed at higher loading) [41] and 10 mol % for HNTf 2 . A progressive increase of the yield was observed when solvents with high polarity (CH 3 CN and DMF vs toluene, CH 2 Cl 2 , CHCl 3, and THF) were used (entries [11][12][13][14][15][16][17][18][19][20][21][22], suggesting the formation of a solvent-stabilized polar intermediate (see mechanistic discussion below). Finally, control experiments were performed in the absence of either PXX, light irradiation, or DIPEA, with no dearomatized products being observed (Table 1, entries 8-10).…”
Section: Pxx As Homogenous Reductive Photocatalystmentioning
confidence: 99%
See 2 more Smart Citations
“…We envisaged that an electrochemical reactor concept that combines flow processing capabilities with a spinning cylinder electrode design should provide a solution to the aforementioned drawbacks of parallel plate reactors. In particular, an assembly of two concentrical cylindrical electrodes (anode and cathode) in which the central working electrode spins around its axis should provide excellent mixing and thus mass transport, even at very low flow rates, while maintaining a relatively narrow interelectrode gap. , The efficient mixing attained with the system should also enable working with solid suspensions without the risk of clogging the system or the accumulation of particles. Moreover, the fact that the central electrode is spinning should provoke rapid detachment of any gas bubbles from the surface of the electrodes, facilitating their displacement to the reactor headspace and effectively overcoming the issues of gas evolution during electrolysis.…”
Section: Introductionmentioning
confidence: 99%